2018
DOI: 10.1155/2018/5934872
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Depression and Associated Factors among Asthma Patients in Addis Ababa, Ethiopia

Abstract: Background Depression in asthma patients can cause worsening of respiratory symptoms. Addressing mental illness in those with asthma improves asthma outcomes. This study aimed to assess the epidemiology of depression and associated factors among asthma patients attending government hospitals in Ethiopia. Methods Institutional based cross-sectional study was conducted on patients with asthma at three governmental hospitals of Addis Ababa from June to July 2017. Patient health questionnaire (PHQ-9) depression sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…This finding is in line with the magnitude of depression among pregnant women in a study conducted at Malaysia (6.9%) [20]. However, this is lower than studies conducted in three public hospitals of Northwest Ethiopia (51%) [15], Addis Ababa (21%) [21], the pooled prevalence of depression among patients with diabetes in Ethiopia (39.73%) [22], Saudi Arabia (37.4%) [19], China (31.4%) [23], and the three Asian countries (39.1%) [18]. The possible justification for this discrepancy might be the difference in tool, source population, and socioeconomic difference.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding is in line with the magnitude of depression among pregnant women in a study conducted at Malaysia (6.9%) [20]. However, this is lower than studies conducted in three public hospitals of Northwest Ethiopia (51%) [15], Addis Ababa (21%) [21], the pooled prevalence of depression among patients with diabetes in Ethiopia (39.73%) [22], Saudi Arabia (37.4%) [19], China (31.4%) [23], and the three Asian countries (39.1%) [18]. The possible justification for this discrepancy might be the difference in tool, source population, and socioeconomic difference.…”
Section: Discussionsupporting
confidence: 86%
“…The possible justification for this might be the lack of social support for single patients. This finding was consistent with the finding of a study conducted in Addis Ababa [21], Saudi Arabia [19], and Spain [25].…”
Section: Behavioural Neurologysupporting
confidence: 93%
See 1 more Smart Citation
“…52,53 Depression and anxiety are higher in those with uncontrolled compared to controlled asthma, 54 with studies reporting 2-to 8fold higher prevalences. 55,56 Our observation that asthmatic patients with depression as a comorbidity and those with stress-triggered asthma had a similar profile of higher circulating Th2 cells would support the evidence that overlapping inflammatory pathways are mediating these diseases. For instance, depression scores correlate with asthma-related quality of life, 57 and studies in twins suggest that there may be shared genetics between asthma and depression.…”
Section: Discussionsupporting
confidence: 63%
“…The direct health care cost of patients with uncontrolled asthma is four to eight times that of controlled (15,16). Shreds of evidence also revealed that uncontrolled asthma results in higher rates of depression, insomnia, sleep disturbances, and signi cant derangement in health-related quality of life of asthmatic patients (6)(7)(8)(9). Furthermore, patients with asthma will lose an estimated 15.46 million Quality Adjusted Life Years Lost (QALYs) because of uncontrolled asthma in the coming 20 years (10).…”
Section: Introductionmentioning
confidence: 99%